2014
DOI: 10.1002/cplu.201402152
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Accelerated Biocatalytic Oxidation Reactions

Abstract: The influence of (visible) light on the performance of laccase mediator systems (LMS) was investigated. As a model reaction, LMS‐mediated nicotinamide adenine dinucleotide (NAD+) regeneration to promote alcohol dehydrogenase catalyzed oxidation reactions was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Likewise, it has been recently reported that pyrimidine cofactor regeneration to the oxidised form [NAD(P) + ] is feasible employing Myceliophthora thermophila laccase, ( Mtlac ), O 2 as final electron acceptor and dyes (methylene blue, methylene green and azure B) as mediators, as shown in Scheme . In this report, the authors were able to demonstrate that, upon visible light irradiation, the NADH oxidation is three orders of magnitude faster than the obscure counterpart.…”
Section: One‐pot Processes Combining Biocatalysts and Non‐traditionalmentioning
confidence: 66%
See 1 more Smart Citation
“…Likewise, it has been recently reported that pyrimidine cofactor regeneration to the oxidised form [NAD(P) + ] is feasible employing Myceliophthora thermophila laccase, ( Mtlac ), O 2 as final electron acceptor and dyes (methylene blue, methylene green and azure B) as mediators, as shown in Scheme . In this report, the authors were able to demonstrate that, upon visible light irradiation, the NADH oxidation is three orders of magnitude faster than the obscure counterpart.…”
Section: One‐pot Processes Combining Biocatalysts and Non‐traditionalmentioning
confidence: 66%
“… Use of a bienzymatic system laccase‐ADH coupled with dyes as mediators for the photooxidation of cyclohexanol to cyclohexanone …”
Section: One‐pot Processes Combining Biocatalysts and Non‐traditionalmentioning
confidence: 99%
“…[9a, 10] Also here, under certain circumstances, visible light can accelerate this process. [11] In addition to the aforementioned organic dyes, also inorganic semi-conductors have been used as photocatalysts to accelerate the (aerobic) reoxidation of NAD(P)H. For example, TiO 2 has been reported by Tanaka and coworkers for this purpose. [12] Next to its function as photocatalyst, TiO 2 also served as carrier material to immobilize the ADH (from horse liver, HLADH) and enabled using a near-neat reaction system (Scheme 7).…”
Section: Ni Et Hollmannmentioning
confidence: 99%
“…Hollmann was highlighted here when he won the Jochen Block Prize 5a. His report on light‐accelerated biocatalytic oxidation reactions was featured in the Early Career Series in ChemPlusChem 5b…”
Section: Awarded …︁mentioning
confidence: 99%